Distribution of serotonin positive mast cells in the intrapulmonary airways of rats - Ivanova, Ivelina; Tomov, Nikola; Dimitrov, Nikolaj; Atanasova, Dimitrinka; Sivrev, Dimitar; Stefanov, Ivaylo (Dokladi na Bălgarskata Akademija na Naukite, 2019)
Based on the scarce information about the expression of serotonin by mast cells in normal rat lung, we aimed to describe in detail the distribution of these cells in the wall of bronchi and bronchioles, as well as in the interalveolar septa. To visualize serotonin-positive mast cells a toluidine blue staining was performed immediately after the immunohistochemical staining on the same sections. Thus, we estimated the density of mast cell in different layers of intrapulmonary airways and in alveolar parenchyma. A reduction of mast cell numbers from bronchi to bronchioles, and then to alveolar septa was detected. In conclusion , detailed information about the density of serotonin positive mast cells in the layers of the wall of intrapulmonary airways and alveolar parenchyma is presented. Our findings confirm the role of these cells as one of the main sources of serotonin, which participate in maintaining the homeostasis in the lung.